2015
DOI: 10.15252/emmm.201404571
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of hematogenous tumor metastasis by acid sphingomyelinase

Abstract: Metastatic dissemination of cancer cells is the ultimate hallmark of malignancy and accounts for approximately 90% of human cancer deaths. We investigated the role of acid sphingomyelinase (Asm) in the hematogenous metastasis of melanoma cells. Intravenous injection of B16F10 melanoma cells into wild-type mice resulted in multiple lung metastases, while Asm-deficient mice (Smpd1−/− mice) were protected from pulmonary tumor spread. Transplanting wild-type platelets into Asm-deficient mice reinstated tumor metas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
75
2
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 60 publications
1
75
2
3
Order By: Relevance
“…Additionally, ASM, previously also associated with apoptosis, is emerging as a key tumor promoter (73)(74)(75)). In the pathway described in this study, elevated ceramide may serve as a precursor to higher C-1-P levels which may 'override' the cell intrinsic functions of ceramide by promoting inflammatory and other tumor-promoting effects.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, ASM, previously also associated with apoptosis, is emerging as a key tumor promoter (73)(74)(75)). In the pathway described in this study, elevated ceramide may serve as a precursor to higher C-1-P levels which may 'override' the cell intrinsic functions of ceramide by promoting inflammatory and other tumor-promoting effects.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced cell adhesion upon sphingomyelinase- or ceramide treatment has been reported in different cell types, hinting at a general mechanism [50-52]. Particularly relevant to this study are reports on hematogenous metastasis, indicating that platelets secrete Asm to regulate tumor cell extravasation [51]. Subsequently, this process was shown to involve P-selectin, p38 MAPK and ß1-Integrin [53, 54].…”
Section: Discussionmentioning
confidence: 86%
“…Ceramide has been previously shown to mediate cell adhesion to endothelial cells [28]. These studies indicated that ceramide-enriched membrane platforms cluster adhesion molecules such as β 1 -integrin [28] or ICAM-1 [29].…”
Section: Discussionmentioning
confidence: 99%
“…Ceramide has been previously shown to mediate cell adhesion to endothelial cells [28]. These studies indicated that ceramide-enriched membrane platforms cluster adhesion molecules such as β 1 -integrin [28] or ICAM-1 [29]. Receptor clustering results in a very high local density of cognate receptor molecules, thereby permitting and greatly amplifying signal transduction by this particular receptor.…”
Section: Discussionmentioning
confidence: 99%